Comparable expression of matrix metalloproteinases 1 and 2 in pouchitis and ulcerative colitis. Issue 3 (1st September 2000) - Stallmach, A; Chan, C C; Ecker, K-W; Feifel, G; Herbst, H; Schuppan, D; Zeitz, M
Abstract : BACKGROUND AND AIMS: Matrix metalloproteinases (MMPs) are implicated in the tissue destruction associated with inflammatory diseases. Proctocolectomy with ileo-anal pouch (IAP) anastomosis is associated with pouchitis, particularly in patients with ulcerative colitis (UC). The aim of this study was to quantify MMP-1 and MMP-2 in inflamed and uninflamed pouches of patients with UC compared with those with active UC. IAP patients with familial adenomatous polyposis (FAP) served as controls. METHODS: Biopsies were taken from 33 patients with IAP (UC, n=25; FAP, n=8) and from 10 UC patients. MMP-1 and MMP-2 were quantified using sandwich enzyme linked immunosorbent assays. In addition, northern and western blotting and in situ hybridisation experiments were performed. RESULTS: In pouchitis (n=11), MMP-1 and MMP-2 concentrations were increased compared with uninflamed pouches of patients with UC (n=14) or FAP (n=8) (MMP-1 17.7 ng/mg protein v 7.8 (UC) v 7.6 (FAP), p⩽0.05; MMP-2 16.4 v 9.5 (UC) v 6.3 (FAP), p⩽0.05). Western and northern blots revealed increased MMP-1 and MMP-2 protein and transcript concentrations in inflamed pouches. Mesenchymal cells were identified as major producers of MMP-1 and MMP-2 in pouchitis. A similar increase in MMPs was observed in tissues of patients with active UC. CONCLUSIONS: Our results support the hypothesis that MMPs are involved in mucosal destruction and crypt hyperplasia, as seen in pouchitis.